PENGARUH GREEN INNOVATION DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - nada Yasya; Muchlis Muchlis (Ibs Press, 2024)
This study aims to examine and analyze the effect of Green Innovation and Financial Performance on firm value proxied by Tobin's Q and Price to Book Value. This study uses a multiple linear regression equation model which is processed with Eviews software version 12. The sample for this research is food and beverage sub-sector companies listed on the Indonesian Stock Exchange for the period 2017 – 2021 using a purposive sampling technique. The results showed that Green Innovation has a negative effect on Tobin's Q and Price to Book Value, Return On Assets has a positive effect on Tobin's Q and Price to Book Value, Earnings Per Share has no effect on Tobin's Q and Price to Book Value, and Debt To Equity Ratio has no effect on Tobin's Q, but has a positive effect on Price to Book Value. These results provide an indication that companies in the food and beverage sub-sector in Indonesia that carry out green innovation consider that the disclosure and implementation of this innovation does not result in the company getting rewards from investors in the form of an increase in share prices and financial performance remains a factor that cannot be separated from investors' assessment of firm value.